2004
DOI: 10.1177/159101990401000102
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Haemorrhagic Telangiectasia Cerebrospinal Localization in Adults and Children

Abstract: Cerebral arteriovenous malformations (CAVM) can be associated with Hereditary Haemorrhagic Telangiectasia (HHT), adominantly inherited vascular disorder with variable penetrance and expressivity. The presentation and angiographic features were analysed retrospectively. The purpose is to point to special groups of AVM patients within the overall CAVMs and to discuss the issue of screening. We reviewed 34 cases of HHT -related CAVM from the data bank in Bicêtre from 1985–2003. In Spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…As pointed out by Fulbright et al, MRI might underestimate HHT-related vascular malformations; however, the large (and potentially dangerous) lesions such as arteriovenous malformations and AV fistulae are readily detectable on routine sequences [6]. The micro-AVMs on the other hand might remain unnoticed on MRI; however, the latter do not tend to bleed in the HHT population [25,26]. Therefore, MRI might constitute an apt method for screening patients with HHT for neurovascular manifestations.…”
Section: Imaging Appearances and Angioarchitecture Of Neurovascular Mmentioning
confidence: 99%
See 3 more Smart Citations
“…As pointed out by Fulbright et al, MRI might underestimate HHT-related vascular malformations; however, the large (and potentially dangerous) lesions such as arteriovenous malformations and AV fistulae are readily detectable on routine sequences [6]. The micro-AVMs on the other hand might remain unnoticed on MRI; however, the latter do not tend to bleed in the HHT population [25,26]. Therefore, MRI might constitute an apt method for screening patients with HHT for neurovascular manifestations.…”
Section: Imaging Appearances and Angioarchitecture Of Neurovascular Mmentioning
confidence: 99%
“…The twelve micro-AVMs were equally distributed in patients under and over 15 years of age (six each), whereas of the eight small AVMs seven occurred in adults [25]. Mahadevan et al evaluated 39 patients with HHT but did not specifically look at the age distribution of the different phenotypical appearances [26]. Fulbright et al have reported on the thus far largest group of patients with HHT, however, they mainly focused on MRI and performed angiography only in a small number of cases.…”
Section: Age Dependencymentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary AVMs are the most common visceral AVM in HHT patients, affecting as many as 37%-59% of adult HHT patients [1]. Spinal AVM/AVFs, a rare presentation of HHT, are seen in 4.5%-8% of patients according to the largest series [5][6].…”
Section: Introductionmentioning
confidence: 99%